Enhancing a blended module in General Didactics: new contents, materials, forms of assessment and feedback - Lilia Teruggi; Franca Zuccoli; Francesca Bassi (Firenze University Press, 2019)
In this paper, we examine developments in the blended version of the module in General Didactics within Milano-Bicocca University's Master's Degree in Primary Education program, focusing on the learning activities offered to students and the use of feedback to support their learning processes. Over the three years since the introduction of the blended format, the number of students enrolled has quadrupled. The interactions between teachers and students on the e-learning platform offer a set of valuable insights concerning amongst other aspects cooperation among students during on-campus activities as a form of peer education, new forms of assessment, and the provision of feedback on individual learning activities. We discuss the overall experience of the past three years and how the blended module may be further enhanced in the future by increasing the level of interaction between lecturers/tutors and students, as well as among students.   Il corso di Didattica Generale, l'evoluzione del corso blended. La proposta di nuovi contenuti, materiali, prove e uso del feedback. Il presente contributo vuole presentare una riflessione sull'evoluzione del corso di Didattica Generale, del Corso di Laurea in Scienze della Formazione Primaria, Università di Milano-Bicocca, erogato in modalità blended. Nello specifico l'attenzione si è concentrata sulle attività proposte ai corsisti, unite all'uso del feedback come modalità di sostegno nel percorso di formazione. Durante i tre anni che hanno visto la creazione di un nuovo progetto legato a questo corso, il numero degli studenti iscritti è più che raddoppiato. Dalle interazioni dei docenti e da alcune risposte raccolte risultano particolarmente significativi alcuni elementi, ma qui si vuole fin da subito sottolineare l'importanza sia del lavoro tra studenti in presenza, nell'ottica di una proposta di peer-education, come pure dell'individuazione di nuove prove richieste ai frequentanti di questo corso, unite alla modalità di risposta legate alle singole attività. Il contributo racconta di una prima esperienza che vuole svilupparsi nell'ottica di un maggior incremento delle interazioni di docenti e tutor con gli studenti, e degli studenti tra loro.